Targeting Complement Pathways During Cold Ischemia and Reperfusion Prevents Delayed Graft Function. Issue 9 (8th April 2016) - Yu, Z. X.; Qi, S.; Lasaro, M. A.; Bouchard, K.; Dow, C.; Moore, K.; Wu, Z.; Barama, A.; Xu, J.; Johnson, K.; Marozsan, A. J.; Wang, Y.
Abstract : The complement system plays a critical role in ischemia–reperfusion injury (IRI)–mediated delayed graft function (DGF). To better understand the roles of complement activation pathways in IRI in kidney transplantation, donor kidneys were treated ex vivo with terminal complement pathway (TP) inhibitor, anti‐rat C5 mAb 18A10, or complement alternative pathway (AP) inhibitor TT30 for 28 h at 4°C pretransplantation in a syngeneic kidney transplantation rat model. All 18A10‐ and 67% of TT30‐pretreated grafts, but only 16.7% of isotype control‐pretreated grafts, survived beyond day 21 (p < 0.01). Inhibitor treatment in the final 45 min of 28‐h cold ischemia (CI) similarly improved graft survival. Systemic posttransplant treatment with 18A10 resulted in 60% increased graft survival beyond day 21 (p < 0.01), while no TT30‐treated rat survived > 6 days. Our results demonstrate that AP plays a prominent role during CI and that blocking either the AP or, more effectively the TP prevents ischemic injury and subsequent DGF. Multiple complement pathways may be activated and contribute to reperfusion injury; blocking the TP, but not the AP, posttransplant is effective in preventing reperfusion injury and increasing graft survival. These results demonstrate the feasibility of using complement inhibitors for prevention of DGF in humans. Abstract : Blockade of a specific complement pathway during cold ischemia or reperfusion reduces ischemia–reperfusion injury and the subsequent development of delayed graft function in a syngeneic kidney transplantation rat model.